Follow the heart: A tale of possible infective endocarditis in a patient co-infected with Methicillin-resistant Staphylococcus aureus and Severe Acute Respiratory Syndrome Coronavirus 2 - Cozac Dan-Alexandru; Sîrbu Ileana Voichiţa; Scridon Alina (Sciendo, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is a leading pathogen responsible for bacteremia and valvular endocarditis. In patients with Coronavirus Disease 2019 (COVID-19), MRSA co-infection represents a challenging scenario, with increased morbidity and mortality.